Interprofessional Action for Oral Health Building a Dignified Life Through Education and Care - Azzah, Afaf Aqilah; Pratiwi, Diara Urnayla; Yuanita Anwaristi, Aprilia (Universitas Tunas Pembangunan Surakarta, 2025)
Interprofessional Collaboration (IPC) is a partnership between individuals from different professional backgrounds who work together to solve health problems and provide health services. IPC occurs when various health professions collaborate with patients, families, and communities to provide comprehensive, high-quality car. The goal of interprofessional collaborative community service activities (dental and oral health screening and counseling) is to increase public awareness, attitudes, and behaviors regarding dental and oral health care. Interact and communicate directly with students regarding economic, social, and health conditions. Apply the knowledge gained in lectures to the community. The activity was carried out with the following series: a. Preparation Stage, b. Implementation Stage, and c. Evaluation Stage. This activity received a warm welcome from kindergarten children, MA MTQ students, and members of the Bulu PCM who participated enthusiastically. However, there were several challenges that need to be addressed for similar activities in the future, such as the number of community participation that did not meet the target and internal miscommunication regarding the target participants. In addition, public hesitation towards health checks indicated the need for a more educational and persuasive approach